PdII‐Catalyzed Purine‐Directed Ortho Nitration of 6‐Arylpurines by C(sp2)–H Activation: A Practical Approach to Synthesize 6‐(2‐Nitroaryl)‐Purine Derivatives. Issue 30 (25th July 2018) - Gou, Quan; Li, Wenxi; Zhao, Qingsheng; Xie, Jia; Luo, Ping; Cao, Guang; Chen, Suiyun; Qin, Jun
Abstract : Herein we report a method for Pd II ‐catalyzed purine‐directed ortho nitration of 6‐arylpurines via C(sp 2 )–H activation by using t BuONO/O2 as nitration agent. This procedure is highly efficient and produces a range of 6‐(2‐nitroaryl)‐purine derivatives with good chemoselectivity and functional‐group tolerance. The utility of the method is further illustrated in the synthesis of antibacterial agent. Abstract : 6‐(2‐Nitroaryl)‐purine can be obtained through Pd II ‐catalyzed C(sp 2 )–H activation of 6‐arylpurines in the presence of t BuONO/O2 . The purine substituent acts as an ortho directing group for the nitration.